Statistical analysis of variability properties of the Kepler blazar W2R 1926+42. Issue 1 (28th April 2018) - Li, Yutong; Hu, Shaoming; Wiita, Paul J; Gupta, Alok C
Abstract: We analysed Kepler light curves of the blazar W2R 1926+42 that provided nearly continuous coverage from quarter 11 to quarter 17 (589 d between 2011 and 2013) and examined some of their flux variability properties. We investigate the possibility that the light curve is dominated by a large number of individual flares and adopt exponential rise and decay models to investigate the symmetry properties of flares. We found that those variations of W2R 1926+42 are predominantly asymmetric with weak tendencies towards positive asymmetry (rapid rise and slow decay). The durations ( D ) and the amplitudes ( F 0 ) of flares can be fit with lognormal distributions. The energy ( E ) of each flare is also estimated for the first time. There are positive correlations between log D and log E with a slope of 1.36, and between log F 0 and log E with a slope of 1.12. Lomb--Scargle periodograms are used to estimate the power spectral density shape. It is well described by a power law with an index ranging between −1.1 and −1.5. The sizes of the emission regions, R, are estimated to be in the range of 1.1 × 10 15 –6.6 × 10 16 cm. The flare asymmetry is difficult to explain by a light travel time effect but may be caused by differences between the time-scales for acceleration and dissipation of high-energy particles in the relativistic jet. A jet-in-jet model could also produce the observed lognormal distributions.